EU development policy and climate change - Andrey Samarskiy; Maria Waldinger (CESifo GmbH, 2024)
The Samoa Agreement in November 2023 marks an expansion of the EU's core areas of development cooperation. This article shows how climate change affects other priority areas of economic, political and social development. Two adaptation measures deserve more attention: The EU development policy should support innovation in financial mechanisms for family farms to mitigate the negative effects of climate-related income shocks. In addition, it can bring about lasting structural change by reducing transport costs, thereby promoting greater openness in product markets and the free movement of people.
Keywords: 330